Characteristics and Behaviour of Transient Current during Fault Occurrence on Hybrid Overhead line and Underground Cable Distribution System - Tussanai Satharpornmongkollert; Atthapol Ngaopitakkul; Chaichan Pothisarn (My University, 2015)
This paper proposes to study characteristics of distribution system consisting of overhead line and underground cable in a system when single line to ground fault occurs in the system. For this study, ATP/EMTP simulation is used to simulate current waveform in each case as overhead system, underground system and both of underground and overhead systems, called hybrid system. The current waveform is measured at sending end side for analysis when fault occurs. Then, compare the hybrid system result with overhead and underground system results for observing different points. The characteristics from analysis are used to plan and design system protection and determine correctly protection equipment operations.
Keywords: Emtp; Transient (computer programming); Overhead line; Line (geometry); Power Systems Fault Detection